Rehabilitation of An Analgesic Bracelet Based on Wrist-Ankle Acupuncture in Patients with Rotator Cuff Injury: A Randomized Trial - Wenjuan Song; Xin Wang; Jishen Zhou; Ping Shi; Wei Gu; Fanfu Fang (Pain Research and Management)
Objective. To evaluate the effect of transcutaneous electrical nerve stimulation (C-TENS) in the rehabilitation of rotator cuff injury. Methods. A total of 60 patients diagnosed with mild to moderate rotator cuff injury were randomly divided into the control group and test group. Both groups received conventional rehabilitation treatment including physical therapy, joint mobilization, interventional therapy, and family recovery training. The test group additionally received TENS treatment on the upper area 4 or 5 of the wrist, based on the wrist-ankle acupuncture (WAA) theory. The results of the visual analogue scale (VAS), shoulder range of motion (ROM), and Constant-Murley score (CMs) were collected before and after the 1st treatment and after the 5th treatment. The differences of those indicators between the two groups were analyzed statistically. Results. The VAS scores of measurement points after treatment were all improved compared with those at baseline. There was a significant difference between the two groups after the 1st and the 5th treatment (p<0.05), and the improvements in the test group were better than those in the control group. The ROM of flexion, extension, abduction, adduction, internal rotation, and external rotation after the 1st treatment and 5th treatment in both groups were all improved compared with those at baseline. There was no significant difference between two groups. The CMs of the two groups after the 5th treatment were all improved compared with those at baseline. There was no significant difference between two groups. No adverse events occurred during the treatment. Conclusion. Electrical stimulation on the wrist combined with conventional rehabilitation is more effective in relieving pain than the conventional rehabilitation alone. Electrical stimulation on the wrist combined with conventional rehabilitation has no obvious effect in improving shoulder joint mobility and shoulder function.